Calculation algorithm development of pulling ability of drivegear and conveyor belt tensioners - Кіктєв, Микола Олександрович (Technology audit and production reserves, 2014)
The article is devoted to development an algorithm and software for automated calculation of the conveyor tractive factor value. The basis is known calculation method, it is discussed various variants of conveyor - single and double-drum, with clamping roller or tape, hard kinematical or independent connection between drums. It is formalized the second stage of automated design problem of mining conveyors, using known methods approved by Standard. A visual form for user interface based on example of basic parameters of the mine conveyor that was created in the Visual Basic for Application programming language. Visual Basic for Application programming language, built-in MS Office package, is used for automate the calculation of these conveyor parameters, the visual form of algorithm realization calculating of the traction drive capacity conveyor drive gear pulling ability is developed. Depending on the number of drums, used in the conveyor, it is chosen the mode and type of drive. For single-drum drive gear is chosen the classic drive gear: with clamping roller or clamping tape. For double-drum drive gear is chosen the drive gear type: with hard kinematical or independent connection between drums.